Mrs. Columbo word games - Sagal, Boris; McAdams, James ([Los Angeles, Calif. Universal TV], 1979)
Kate Columbo is wife to a police lieutenant, a mother, homemaker and reporter for a neighborhood newspaper. In the series' opener, she also demonstrates a knack for investigation after she overhears a neighbor plotting the murder of his wife.
VHS.
Kate Mulgrew, Frederic Forrest.
Keywords: Columbo, Mrs. (Fictitious character).